Modernization and Relevance of Islamic Economics in Improving Social and Economic Welfare - Arief, Arief Sarjono; Andyka Reyza, Andyka Reyza (Cattleya Darmaya Fortuna, 2023)
Modernization of Islamic economy plays a significant role inimproving social and economic welfare by offering a moreinclusive, equitable and sustainable financial system. Keyelements such as Islamic Banking, Islamic Fintech and IslamicMicrofinance show a significant impact in expandingfinancial access and economic empowerment, while socialinstruments such as Waqf and Zakat play a significant role inpoverty alleviation and wealth distribution. Although Sukukand Islamic ESG contribute to economic growth, their impacton social welfare tends to be more limited. The results of thisanalysis show that modern Islamic economy has the potentialto offer more equitable and sustainable solutions, but stillfaces challenges in implementation and adaptation to currentglobal needs. Therefore, strategic steps are needed such asinnovation in Islamic economic instruments, utilization oftechnology, improvement of education and internationalcollaboration to optimize its impact on society